Reporter's notebook, volume 3 - Manicad, Jiggy; Pulido, Maki; Philippines. Armed Forces of the Philippines; GMA News & Public Affairs (Quezon City GMA News & Public Affairs, 2013)
Collection of best episodes of Reporter's notebook, an investigative news magazine television show in the Philippines aired every Tuesday night by GMA Network.
Pilipinas for sale? -- Ahensiyasat: Armed Forces of the Philippines -- Upuan -- Black sand mining-- Huling hantungan -- Labor of death.
PG (Parental Guidance)
DVD
In Tagalog, with English subtitles.
Keywords: Protected areas; Cemeteries; Pregnancy; Philippines -- Social conditions; Nonfiction television programs; Documentary television programs